Hubungan Tingkat Pendidikan, Pengetahuan, dan Sikap Dengan Stigma Diri Pada Pasien TB Paru Sensitif Obat di RSUD Kota Mataram - Sofiatuddinia Sofiatuddinia; Risky Irawan Putra Priono; Wendy Handayani; Alfian Muhajir (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Indonesia ranks second globally in the number of tuberculosis (TB) cases. TB patients experience not only physical impacts but also social problems in the form of self-stigma. Self-stigma is the process of internalizing stigma from the surrounding environment, which can lead to psychological stress, reduced social functioning, and low adherence to medication. Factors such as educational level, knowledge, and attitudes are thought to play a role in the development of self-stigma among TB patients. This study aimed To determine the relationship between educational level, knowledge, attitudes, and self-stigma among drug-sensitive pulmonary tuberculosis patients at Mataram City Regional General Hospital 2025. This study employed a quantitative analytic observational design with a cross-sectional approach. The sampling technique used was consecutive sampling, with a total of 78 respondents. Data were analyzed using the Spearman rank dan Chi-square test. The results of the univariate analysis showed that most respondents had low levels of self-stigma 69 (88,5%), basic educational attainment 29 (37,2%), sufficient knowledge 58 (74,4%), and positive attitudes 68 (87,2%). Bivariate analysis There was no significant relationship between attitudes and self-stigma (p=0,324). In contrast, educational level (p=0,017) and knowledge (p=0,000) showed significant relationships with self-stigma. Educational level and knowledge have a significant relationship with selfstigma among drug-sensitive pulmonary tuberculosis patients, whereas attitudes do not show a significant relationship. Keywords: Educational Level, Knowledge, Attitude, Self-Stigma, Tuberculosis, Drugsensitive. ABSTRAK Indonesia merupakan negara dengan jumlah kasus tuberkulosis (TB) tertinggi kedua di dunia. Pasien TB tidak hanya mengalami dampak fisik, tetapi juga masalah sosial berupa stigma diri. Stigma diri adalah proses internalisasi stigma dari lingkungan sekitar yang dapat menyebabkan stres psikologis, penurunan fungsi sosial, serta rendahnya kepatuhan minum obat. Faktor tingkat pendidikan, pengetahuan, dan sikap diduga berperan dalam terbentuknya stigma diri pada pasien TB. Tujuan Penelitian adalah mengetahui hubungan antara tingkat pendidikan, pengetahuan, sikap dan stigma diri pada pasien TB paru SO di RSUD Kota Mataram. Metode penelitian ini kuantitatif analitik observasional dengan desain penelitian cross sectional. Teknik pengambilan sampel menggunakan consecutive sampling. Sampel penelitian sebanyak 78 responden. Data dianalisis dengan uji spearman rank dan Chi-square. Hasil analisis univariat menunjukkan sebgaian besar responden tingkat pendidikan dasar 29 (37,2%), pengetahuan cukup 58 (74,4%), Sikap positif 68 (87,2%), stigma diri rendah 69 (88,5%). Hasil analisis bivariat menunjukkan Tidak terdapat hubungan signifikan antara sikap dengan stigma diri (p=0,324). Sebaliknya, tingkat pendidikan (p=0,017), dan pengetahuan (p=0,000) menunjukkan hubungan signifikan dengan stigma diri. Kesimpulan penelitian ini adalah tingkat pendidikan, pengetahuan memiliki hubungan signifikan dengan stigma diri pasien TB Paru SO, sedangkan sikap tidak menunjukkan hubungan yang signifikan. Kata Kunci: Tingkap Pendidikan, Pengetahuan, Sikap, Stigma diri, Tuberkulosis, Sensitif obat.